2014
DOI: 10.1590/s1678-86212014000400012
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias para a minimização da emissão de CO2 de concretos

Abstract: A maior parte das emissões do concreto originam-se na produção do cimento. A estratégia tradicional de minimização da pegada de CO2 tem privilegiado o grau de substituição do clínquer. No momento atual estima-se que a indústria cimenteira utilize toda a escória de alto forno gerada no país e a quase totalidade das cinzas de melhor qualidade. Desta forma, aumentando a demanda de cimento, a produção de clínquer aumenta, e o teor de adições no clínquer diminui dentro das extensas faixas permitidas pelas normas té… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 8 publications
0
14
0
6
Order By: Relevance
“…These authors demonstrated there is total viability in the industrial production of concrete with ECM of the 3.0 and 4.0 kg/MPa. Other researchers [26] identified that the concretes produced with commercial cements presents performance, in relation to the binder consumption/strength, in the range of 7 to 9 kg/MPa. These values are close to those obtained in this study (6.7 to 7.6 kg cementitious materials/MPa).…”
Section: Results Obtained With the Concretesmentioning
confidence: 99%
“…These authors demonstrated there is total viability in the industrial production of concrete with ECM of the 3.0 and 4.0 kg/MPa. Other researchers [26] identified that the concretes produced with commercial cements presents performance, in relation to the binder consumption/strength, in the range of 7 to 9 kg/MPa. These values are close to those obtained in this study (6.7 to 7.6 kg cementitious materials/MPa).…”
Section: Results Obtained With the Concretesmentioning
confidence: 99%
“…If everyone were to implement this strategy, there would be an insufficient supply of these admixtures to lower the content of clinker significantly on a global scale [3,24]. Therefore, the decrease of the CO 2 footprint of a concrete must also be achieved by strategies of optimization of the use of binders -summarizing, designing to achieve the same level of performance with lower total binder content, whatever the binder.…”
Section: Cement Use Efficiencymentioning
confidence: 99%
“…They also conclude that in order to reduce the environmental impact generated by a structure, the focus should be on the first phase of the study, i.e., the production of raw materials, transportation and production of concrete. Oliveira et al (2014), in their study in Brazil, report that most concrete emissions originate in the cement production and a traditional strategy of minimizing the CO 2 footprint has favored the degree of clinker replacement. They indicated that in relation to the quality control of the productive process of the concrete, there will be a maximum increase of 13% in the total consumption of cement.…”
Section: Recent Studies On Emissions Of Carbon Dioxide Of Reinforced mentioning
confidence: 99%
“…Kim et al (2016) If concrete mix and raw material suppliers were carefully selected, it can be obtained a reduction of 34% in the emission of CO 2 and 1% in the costs Park et al (2012) CO 2 emissions increase linearly with the compressive strength of the concrete; to similar strengths, the concrete produced in the winter presented an increase of approximately 5% in the CO 2 emissions Santoro and Kripka (2016) Higher strength concrete will produce a greater amount of CO 2 ; the CO 2 emissions during transport are significant Choi et al (2016) For smaller loads the increase of the transversal area of concrete is more advantageous for the eduction of O 2 emissions, and for greater loads the increase of the steel profile produces a more sustainable solution Berndt (2015) The use of smaller resistances is advantageous in relation to CO 2 emissions; the choice of the concrete mixture strongly influences the magnitude of the CO 2 emissions Yang et al (2015) The intensity of CO 2 emissions gradually decreases as Portland cement is replaced by complementary cementitious materials (up to 20%) García-Segura et al (2014) In comparison to Portland cement, despite the reduction in CO 2 capture and life time, 80% blast furnace slag cement emitted 20% less CO 2 per year Cabello et al (2016) To reduce the environmental impact generated by a structure, the focus should be on phases of production of raw materials, transportation and production of concrete Oliveira et al (2014) It is not appropriate to base decisions on the emissions of concrete solely on the strength of the concrete and the type of cement used, since the variations are significant Paya-Zaforteza et al (2009) Minimization of embedded CO 2 emissions and economic cost seem to be highly related Park et al (2013) Reducing the amount of steel and increasing the amount of concrete can be an effective way to reduce the structural costs and CO 2 emissions of columns Habert and Roussel (2009) It is also possible to combine cement replacement and increase mechanical strength Possan et al (2016) Concrete during its life time can absorb from 40 to 90% of CO 2 emitted in the manufacturing process; the absorption of CO 2 is directly proportional to the surface area of concrete exposed to CO 2 , and influenced by the type of cement and resistance to concrete. Park et al (2014) Increasing the strength of the structural materials used is more efficient in reducing CO 2 emissions and costs than increasing the quantities of structural materials used Collins (2013) If carbonation is ignored, emission estimates can be overestimated by up to 45% depending on the strength of the concrete that was used as well as the type of construction application that incorporates recycled concrete during the second generation Yepes et al (2012) CO 2 emissions and costs are closely related.…”
Section: Recent Studies On Emissions Of Carbon Dioxide Of Reinforced mentioning
confidence: 99%
See 1 more Smart Citation